Strategi Penanaman Karakter Kedisiplinan pada Siswa SMA - Subando, Joko; Sukari, Sukari; Wauran, Meissara Putri Andannari (TSAQOFAH, 2026)
Low levels of student discipline at the senior high school level, as reflected in violations of school rules, weak learning commitment, and poor self-control, remain a serious challenge in the field of education. This study aimed to analyze strategies for cultivating disciplinary character among senior high school students through systematically implemented educational approaches within the school environment. A descriptive qualitative method with a case study design was employed, using in-depth interviews, participatory observation, and document analysis involving the principal, teachers, guidance and counseling teachers, and students. Data analysis was carried out through the stages of data reduction, data display, and conclusion drawing, strengthened by source and technique triangulation to ensure data trustworthiness. The findings show that disciplinary character is nurtured through educators’ role modeling, consistent enforcement of school rules, integration of discipline values into the learning process, habituation programs, and collaboration between the school and parents. These strategies lead to improvements in punctuality, sense of responsibility, compliance with school regulations, and student independence. The study concludes that comprehensive, continuous, and value-based character-building strategies play an essential role in strengthening disciplinary character among senior high school students, with implications for the need for institutional commitment and a collaborative educational environment to support ongoing character development.